2020
DOI: 10.1108/ijppm-04-2019-0161
|View full text |Cite
|
Sign up to set email alerts
|

Strategic human resource management and employees' intention to leave: testing the moderated mediation

Abstract: PurposeThe purpose of this study is to examine the relationship between business strategies (i.e. cost reduction, quality enhancement and innovation strategy) and employees' intention to leave (ITL), through the mediating role of high-performance work system (HPWS). It also attempts to study variability in the relationship between business strategies, HPWS and employees' ITL on the basis of nature and ownership forms of the firms.Design/methodology/approachPrimary data based on 573 respondents from 192 organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…Moreover, to intensely recognize the impact of CAHRP, a supplementary analysis was done. But, the inefficiency of individual CAHRP in satisfying the employees explained that HR practices collectively were able to produce synergy effect (Kundu et al. , 2020; Kundu and Gahlawat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to intensely recognize the impact of CAHRP, a supplementary analysis was done. But, the inefficiency of individual CAHRP in satisfying the employees explained that HR practices collectively were able to produce synergy effect (Kundu et al. , 2020; Kundu and Gahlawat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This study offers certain implications for the healthcare managers and practitioners. Firstly, it is evident that HR practices create value for the organizations in various business contexts (Garg, 2019) and therefore developing HR competence by investing in Highperformance work systems HPWS consistent with the organizational strategy would advance the role of HR functions (Kundu et al, 2021). In this context, the development of HPWS in the healthcare organizations enhances improved patient outcomes (Kloutsiniotis and Mihail, 2017) and an increased focus on promoting HPWS with employee favourable practices at the operational level would help the managers understand and improve the ground reality in the highly stressful hospital environments.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In this regard, Perez-Lopez et al (2005) show that high-performance human resource practices, including selective hiring, strategic training, contingent compensation and employees' participation in management decision-making, are related to business performance in Spanish companies. In addition, Kundu et al (2021), in a sample of 192 Indian organizations, measured high-performance work systems (HPWSs), along eight dimensions/HR practices, including extensive training, performance-based appraisal, rigorous recruitment and selection, compensation, empowerment, human resource planning, flexible work arrangements and self-managed teams. This study indicated that HPWSs mediate the relationship between business strategy and employees' intention to leave.…”
Section: Strategic Human Resource Practicesmentioning
confidence: 99%